1997
DOI: 10.1017/s0017089500032250
|View full text |Cite
|
Sign up to set email alerts
|

Automatic continuity of certain isomorphisms between regular Banach function algebras

Abstract: Abstract. Let A and B be regular semisimple commutative Banach algebras; that is to say, regular Banach function algebras. A linear map T denned from A into B is said to be separating or disjointness preserving if/.g = 0 implies Tf.Tg = 0, for all f,g e A In this paper we prove that if A satisfies Ditkin's condition then a separating bijection is automatically continuous and its inverse is separating. If also B satisfies Ditkin's condition, then it induces a homeomorphism between the structure spaces of A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…Indeed, a little more can be said with the same argument. One can find a generalized version of the Banach-Stone theorem in [4] to finish a proof of the following Proposition 4.1. Every surjective 2-local automorphism of a regular uniform real or complex function algebra is an automorphism.…”
Section: -Local Automorphisms Of C * -Algebrasmentioning
confidence: 99%
“…Indeed, a little more can be said with the same argument. One can find a generalized version of the Banach-Stone theorem in [4] to finish a proof of the following Proposition 4.1. Every surjective 2-local automorphism of a regular uniform real or complex function algebra is an automorphism.…”
Section: -Local Automorphisms Of C * -Algebrasmentioning
confidence: 99%
“…In [9], we extended the definition of disjointness preserving mappings to the class of regular Banach function algebras. Let us recall that a linear map T defined from a regular Banach function algebra A into such an algebra B is said to be disjointness preserving or separating if f · g ≡ 0 implies T (f ) · T (g) ≡ 0 for all f, g ∈ A.…”
mentioning
confidence: 99%
“…Next we gather the main results concerning disjointness preserving maps between regular Banach function algebras, which can be found in [9]:…”
mentioning
confidence: 99%
“…It is clear that a homomorphism preserves disjointness of cozero sets of functions, hence is a disjointness preserving operator. In [6,7], Font studied bounded disjointness preserving bijections between Fourier algebras, and showed that such an operator is a weighted composition operator. In a recent paper [1], the authors introduced the concept of property (A) and studied such maps in the setting of Banach algebras with property (A).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we completely characterize such operators in the case the involved groups are amenable. Our characterization takes into account the algebraic structure of the underlying groups, and not only their topology, which was the primary emphasis in [6,7].…”
Section: Introductionmentioning
confidence: 99%